How empty was the northwestern Delta before the Ptolemies came? - Schiestl, Robert (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2020)
Archaeological survey work around Buto (Tell elFara'in) provided very little evidence for pre-Ptolemaic settlements.· While this stands in contrast to the settlement history of Buto itself, it fits into an established historical narrative of Ptolemaic land reclamation and settlement foundations. The singular case of a regional pre-Ptolemaic settlement, Korn Asfar, which seems to date to the Third Intermediate Period, is discussed in detail. Taking textual sources, in particular the Satrap Stela, as a starting point, different aspects of the landscape are discussed in combination with geophysical and archaeological evidence: the physical landscape, the political landscape, the strategic landscape, and the settled landscape. In conclusion, methodological reasons for the lack of pre-Ptolemaic archaeological evidence are put forward. Not only was the northwestern Delta developed and settled in pre-Ptolemaic times, but the northern Delta regions are considered as possible models and training grounds for the land reclamation of the Fayum implemented under the Ptolemies.